2021
DOI: 10.52586/5065
|View full text |Cite
|
Sign up to set email alerts
|

Role of the store-operated Ca𝟐+ channel in ATP-induced Ca𝟐+ signalling in mesenchymal stem cells and regulation of cell functions

Abstract: Introduction 3. The SOC/CRAC channel 4. Role of the SOC/CRAC channel in ATP-induced Ca 2+ signalling in MSC 5. Role of the SOC/CRAC channel in ATP-induced regulation of MSC function 6. Concluding remarks 7. Author contributions 8. Ethics approval and consent to participate 9. Acknowledgment 10. Funding 11. Conflict of interest 12. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…It has also been established that cells express a wide range of purine-specific receptors and enzymes that are involved in this molecular machinery [ 93 , 94 , 95 , 96 , 97 ] ( Figure 1 ). Through P-type receptor activation, extracellular nucleotides trigger trophic effects and regulate many processes of MSCs, including proliferation, cell death, migration, and differentiation [ 78 , 93 , 98 , 99 ].…”
Section: Functional Attributes Of Mesenchymal Stem Cells Revisitedmentioning
confidence: 99%
“…It has also been established that cells express a wide range of purine-specific receptors and enzymes that are involved in this molecular machinery [ 93 , 94 , 95 , 96 , 97 ] ( Figure 1 ). Through P-type receptor activation, extracellular nucleotides trigger trophic effects and regulate many processes of MSCs, including proliferation, cell death, migration, and differentiation [ 78 , 93 , 98 , 99 ].…”
Section: Functional Attributes Of Mesenchymal Stem Cells Revisitedmentioning
confidence: 99%
“…A crucial role in the pathogenic mechanism of ACM can be played by the fibro-adipogenic differentiation of cardiac mesenchymal stromal cells (C-MSCs), which renders the cardiac tissue more likely to develop the arrhythmic events leading to the patient’s death [ 2 , 3 ]. Intriguingly, a recent investigation showed that the I c antiarrhythmic drug (AAD) flecainide inhibited fibro-adipose differentiation in human C-MSCs (C-hMSCs) expanded from ACM patients (ACM C-hMSCs) by blocking store-operated Ca 2+ entry (SOCE) [ 4 ], which represents the most important Ca 2+ entry pathway in non-excitable cells [ 5 , 6 , 7 ], including MSCs [ 8 , 9 , 10 ]. Herein, we first describe the genetic background and therapeutic options of ACM.…”
Section: Introductionmentioning
confidence: 99%
“…As a ubiquitous and important second messenger substance, Ca 2+ is widely involved in important pathophysiological processes in cells, and its small changes can affect the normal physiological function of cells. Ca 2+ influx is a key link in the signal transduction process of activation of hepatic stellate cells ( Li et al, 2020 ; Wang et al, 2021a ). Calmodulin (CaM) is widely expressed in various cells.…”
Section: Introductionmentioning
confidence: 99%